Growth, productivity and nutrient concentration of aerobic rice (Oryza sativa L.) under different planting methods, irrigation schedules and soil adjuvant application - Singh, Arjun; Dass, Anchal; Singh, C.V.; Dhar, Shiva; Sudhishri, S.; Das, Kajal; Sarkar, Susheel K. (Annals of Agricultural Research, 2018)
A field experiment was conducted during kharif season of 2016 at Central Rainfed Upland RiceResearch Station (CRURRS), Hazaribagh, Jharkhand to evaluate the effect of planting methods,irrigation scheduling and soil adjuvant on growth, productivity and nutrient content of aerobicrice. The experiment was laid-out in a split-plot design keeping 8-combinations of4-irrigation schedules, viz., I1: Irrigation at 0.9 IW/CPE ratio, I2: Irrigation at 1.2 IW/CPE ratio,I3: Irrigation at 1.5 IW/CPE ratio and I4: Un-irrigated (rainfed) and 2-soil adjuvants (A1: soil adjuvantapplied and A2: No-soil adjuvant) in the main-plots and 2-planting methods (P1: Conventional dryseeding at 20 cm row spacing and P2: Spot-sowing (dibbling of 4-seeds per hill at 20 Ã— 15 cm) in thesub-plots, thus there were a total of 16 treatment combinations. Scheduling irrigation at 1.5 IW/CPE ratio recorded highest plant height (95.4 cm), DMA (1053 g mâ€“2) and LAI (3.44); similarly grainyield increased by 37.3% over rainfed crop, 23% over crop irrigated at 0.9 IW/CPE ratio and 13.5%over 1.2IW/CPE ratio. Effect of irrigation scheduling was found non-significant on nutrientconcentration except P concentration in grain and straw. Crop irrigated at IW/CPE ratio 1.5 exhibitedsignificantly higher P-concentration in grain and straw, over irrigation at IW/CPE ratio 0.9 andrainfed crop. Application of soil adjuvant (APSA 80TM) didn't bring significant changes in any of thestudied parameters. Between the two planting methods, spot-sowing resulted in higher growthand improved grain yield by about 7% over conventional method of sowing, however, effect onnutrient content remained non-significant.